2019
DOI: 10.1016/j.ctrv.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Short-duration versus 1-year adjuvant trastuzumab in early HER2 positive breast cancer: A meta-analysis of randomized controlled trials

Abstract: Background: One year of adjuvant trastuzumab treatment is the standard of care for early stage human epidermal growth factor receptor 2 (HER2)-positive breast cancer patients; however, controversy remains regarding the optimal schedule of trastuzumab because the selection of the 1-year schedule was arbitrary. After the remarkable results of the PERSEPHONE trial as well as the updated final results of the PHARE trial, we performed an updated meta-analysis to reassess the efficacy and safety of shorter durations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…e LN status, another important factor affecting the clinical treatment decisions, has been shown in clinical studies that LN + patients are more likely to benefit from dual-targeting therapy [24,42], but our results suggested that, despite the more pronounced EFS/iDFS benefit in LN + patients, there was no significant interaction between survival and LN status (p � 0.18). Similarly, a recent metaanalysis assessing the optimal duration of trastuzumab treatment also showed no significant interaction between survival and HR status or LN status (p for interaction test, 0.26 and 0.60) [47]. e guidelines recommend using an interaction test for subgroup analyses, as evidenced that inappropriate subgroup-specific analysis was of low reliability and the problem may be underestimated [48].…”
Section: Discussionmentioning
confidence: 99%
“…e LN status, another important factor affecting the clinical treatment decisions, has been shown in clinical studies that LN + patients are more likely to benefit from dual-targeting therapy [24,42], but our results suggested that, despite the more pronounced EFS/iDFS benefit in LN + patients, there was no significant interaction between survival and LN status (p � 0.18). Similarly, a recent metaanalysis assessing the optimal duration of trastuzumab treatment also showed no significant interaction between survival and HR status or LN status (p for interaction test, 0.26 and 0.60) [47]. e guidelines recommend using an interaction test for subgroup analyses, as evidenced that inappropriate subgroup-specific analysis was of low reliability and the problem may be underestimated [48].…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, our meta-analysis is not the first to compare short durations vs. 12 months of trastuzumab, and there are at least six similar meta-analyses or systematic reviews so far (26,27,(36)(37)(38)(39). However, these similar studies were found to have some serious limitations.…”
Section: Discussionmentioning
confidence: 96%
“…A multicenter phase III RCT also showed that the 1-year duration of treatment was associated with an improved DFS (HR = 1.53, 95% CI: 1.16-2.01, P = 0.001) and better OS (HR = 1.61, 95% CI: 1.13-2.29, P = 0.008) among early breast cancer participants treated with trastuzumab concurrently (16). Furthermore, a recent metaanalysis with six RCTs compared the therapeutic effect and toxicity between short durations (9 weeks and 6 months) and 1 year of trastuzumab, and the sub-analyses also showed that patients treated with trastuzumab concurrently in the 1-year group had an improved DFS (HR = 1.22, 95% CI: 1.09-1.38, P = 0.0008) (27). In conclusion, improved survival was more evident among patients treated with concurrent trastuzumab and with ER-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations